CCL22 Recruits CD4-positive CD25-positive Regulatory T Cells into Malignant Pleural Effusion - Qin, Xue-Jun; Shi, Huan-Zhong; Deng, Jing-Min; Liang, Qiu-Li; Jiang, Jing; Ye, Zhi-Jian (Clinical cancer research, 2009)
Purpose: The aim of this study was to explore the presence of the chemokines CCL22 and CCL17 in malignant pleural effusion, and the chemoattractant activity of these chemokines on CD4-positive CD25-positive Foxp3-positive regulatory T cells infiltrating into the pleural space. Experimental Design: The concentrations of CCL22 and CCL17 in both pleural effusions and sera from 33 patients with lung cancer were determined. Flow cytometry was done to determine T lymphocyte subsets in cell pellets of pleural effusion. Pleural cells were analyzed for the expression of CCL22 and CCL17. The chemoattractant activity of CCL22 for regulatory T cells in vitro and in vivo was also observed. Results: The concentration of CCL22 in malignant pleural effusion was significantly higher than that in the corresponding serum. Pleural fluid from lung cancer patients was chemotactic for regulatory T cells, and this activity was partly blocked by an anti-CCL22, but not by an anti-CCL17 antibody. Intrapleural administration of CCL22 of patients produced a marked progressive influx of regulatory T cells into pleural space. Conclusions: Compared with serum, CCL22 seemed to be increased in malignant pleural effusion, and could directly induce regulatory T cell infiltration into the pleural space in patients with malignant effusion.